Shannon Entropy Fits Well Social Risk: Unemployment and Poverty in Large Cities - Nieto-Chaupis, Huber (2019)
We apply the Shannon entropy to model the conjunction of unemployment and poverty in large cities of developing countries. Once the mathematical model has been established, we project the model results to official data resulting in a matching of order of 73% indicating that the social disorder is following a logarithm behavior as consequence of inverse relationship that involve the apparition of poverty in their different manifestations inside of a society that target to be developed in their main aspects.